Integrating machine behavior into human subject experiments: A user-friendly toolkit and illustrations - Christoph Engel; Max R. P. Grossmann; Axel Ockenfels (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2024)
Large Language Models (LLMs) have the potential to profoundly transform and enrich experimental economic research. We propose a new software framework, "alter_ego", which makes it easy to design experiments between LLMs and to integrate LLMs into oTreebased experiments with human subjects. Our toolkit is freely available at github.com/mrpg/ego. To illustrate, we run differently framed prisoner's dilemmas with interacting machines as well as with humanmachine interaction. Framing effects in machine-only treatments are strong and similar to those expected from previous human-only experiments, yet less pronounced and qualitatively different if machines interact with human participants.
Keywords: C91; C92; D91; O33; L86; 330; Software for experiments; large language models; human-machine interaction; framing